Aumento de rebordes edéntulos con autoinjertos óseos de sínfisis mentoniana: estudio piloto - Becerra-Santos, Fabio; Radi-Londoño, José; Otálvaro-Rios, Norman (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The results of edentulous ridge augmentation with mandibular symphysis autogenous bone grafts, performed in 13 patients, 8 women and 5 men, mean age of 40 years (range 16-58 years), are presented in this report. Ridge width increase was made to place osseointegrated implants in resorbed mandible or maxilla due to extractions, periodontal disease, trauma, endodontic infection and other pathologies. In all patients, except one a final width of 5 or more millimeters was achieved. Mean final width was 572mm, to put standard implants (3.75mm.). Bone quality obtained was: Type I (5/13), Type II (7/13), whereas Type III and IV were never present. Mean graft resorption was 45% and there were not mayor postoperative complications in donor or in bed sites. Total success rate was 92.31% and failure 769%, due to flap dehiscence, graft contamination and total resorption in one of the 13 grafted sites. This ridge augmentation procedure is effective, efficient, predictable and cheaper than other guided bone regeneration techniques and autogenous bone grafts from different sites.